Europe and the Black Sea Region A History of Early Knowledge Exchange (1750-1850) - Gutmeyr, Dominik; Kaser, Karl (Studies on South East Europe, 2018)
When the scientific study of the Black Sea Region began in the late 18th and early 19th centuries, initially commissioned by adjacent powers such as the Habsburg and the Russian empires, this terra incognita was not yet considered part of Europe. The eighteen chapters of this volume show a broad range of thematic foci and theoretical approaches - the result of the enormous richness of the European macrocosm and the BSR. The microcosms of the many different case studies under scrutiny, however, demonstrate the historical dimension of exchange between the allegedly opposite poles of `East' and `West' and underscore the importance of mutual influences in the development of Europe and the BSR.